Implementasi Hak Mengajukan Permohonan Pengujian Peraturan Perundangan Di Bawah Undang-Undang Oleh Kesatuan Masyarakat Hukum Adat - Jhon Alberth Latuny; Marthinus Johanes Saptenno; Victor Juzuf Sedubun (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Law Number 3 of 2009 concerning the Supreme Court Article 31A paragraph (2) guarantees the existence of a customary law community unit and has the right to submit an application to the Supreme Court in terms of statutory regulations deemed that their rights are detrimental to the customary law community unit. However, customary law communities, especially in Ambon City, do not exercise their rights.Purposes of the Research: This writing aims to find out how the implementation of the right to submit requests for judicial review of statutory regulations under the law by indigenous peoples according to Article 31A of Law Number 3 of 2009 concerning the Supreme Court. Methods of the Research: The type of research used is juridical empirical. The procedure for collecting legal materials by conducting research in the form of interviews and observations as well as literature study of legal materials, namely primary legal materials and secondary legal materials. Then the legal materials that have been obtained are analyzed descriptively-qualitatively.Results of the Research: The results obtained are that the implementation of the right to file an application has not been carried out properly by the customary law community in Ambon City, due to the lack of action taken by the local government in providing understanding to the community about the rights they have.